A Systematic Review of the Relationship Between Ambulant Status and the Need for a Lights-and-Siren Ambulance Response to Crashes - Ceklic, Ellen; Tohira, Hideo; Ball, Stephen; Finn, Judith (2020)
Introduction: Motor vehicle crashes (MVCs) can result in life-threatening injuries, and ambulances are therefore often dispatched at the highest priority response of lights and-siren (L&S). However, assigning L&S ambulance response based on type of incident alone may result in over-triage, meaning that the patient’s condition did not warrant L&S ambulance response. Potentially, the ambulatory status of the MVC patient at the scene (i.e., whether they can walk) could help inform the ambulance dispatch priority, given that ambulation reflects both a person’s physical ability to walk and their conscious state. The objective of this systematic review is to examine published studies to determine whether ambulatory status of those involved in an MVC can predict the need for L&S ambulance response.